Structure-activity relationship study between baicalein and wogonin by spectrometry, molecular docking and microcalorimetry. (1st October 2016) - Tu, Bao; Li, Rong-Rong; Liu, Zhi-Juan; Chen, Zhi-Feng; Ouyang, Yu; Hu, Yan-Jun
Graphical abstract: Highlights: Multiple methods have been introduced for the structure-activity relationship study. Difference in structure has been firstly used for illustrating the interaction with BSA. The effects of functional group have been discussed thoroughly. Antioxidant and antibacterial activity of baicalein and wogonin has been compared on structural level. Abstract: Flavones (e.g. baicalein and wogonin) extensively used worldwide in food preparation and traditional medicine. In this study, a systematically comparative study of their structure-activity relationships (SAR) on their interaction with BSA, antioxidant activity and antibacterial activity has been carried out by spectrometry, molecular docking and microcalorimetry. Our results show that the skeleton structure of flavones, the number of hydroxyl groups, the type of functional group, conjugated system and the steric hindrance may be responsible for their different biological activity. These findings not only would lay a scientific foundation for discovering and designing flavones-based food and drug, may also help us to understanding the structure-activity relationship between flavones at the molecular level.